Effect of Sensorimotor Rehabilitation Protocol on Vertical Ground Reaction Force and Loading Rate in Men with Patellofemoral Pain: A Randomized Controlled Trial - Ali Yalfani; Mohamadreza Ahmadi; Azadeh Asgarpoor (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: The change of vertical ground reaction force and loading rate rate is a important factor in causing patellofemoral pain (PFP). The aim of this study was the effect of sensory-motor exercises on the vertical ground reaction force and loading rate in patients with PFP when stair descent. Methods: A total of 30 patients with PFP participated and were randomly divided into two experimental and control groups (15 subject in each group). Over a period of twelve weeks, the experimental group engaged in sensorimotor exercises, while the control group did not receive any therapeutic intervention. Pain intensity, fear of movement, quadriceps muscle strength, knee flexion angle, components of vertical ground reaction force and loading rate were evaluated in two stages pre-test and post-test. For data analysis SPSS 16 software and the covariance statistical method were used to compare the results between groups, and the significance level was considered 0.05. Results: The analysis of covariance analysis indicated that sensorimotor exercises in the experimental group compared to the control group had a significant difference in reduced pain (P >0.001), reduced fear of movement (P >0.001), incresed quadriceps muscle strength (P >0.001), incresed knee flexion angle (P >0.001), components of vertical ground reaction force (P >0.001), and reduced loading rate (P >0.001). Conclusion: The finding suggest that the experimental group experienced a boost in in quadriceps muscle strength, leading to diminished pain and fear of movement, an increase in knee flexion angle, and enhanced active shock absorption. Consequently, there was an increase in both peak forces while the loading rate and valley force decreased.